LITERATURE REVIEW IMPACT OF TAX AND SUBSIDY ON REDUCING INCOME INEQUALITY IN INDONESIA - Sakti Prabowo (JURNAL PAJAK INDONESIA, 2017)
Many countries have used fiscal policy Tax and subsidy as a tool to reduce income inequality and many of them have succeeded to achieve it. In contrast, tax and subsidy in Indonesia tend to have a neutral effect on inequality today. This research aims to identify the factors caused Indonesia fiscal policy doesn't have a significant impact on income inequality reduction and what steps should be taken by the government to improve the role of fiscal policy in order to reduce income inequality. From the literature review, this paper finds that Indonesia should improve the quality of public spending.  Indonesia government should Prioritize social spending and infrastructure to improve the fiscal policy role to reduce inequality. In addition, increasing direct tax such as personal income taxes should be done in order to make it more effective.